Rheumatological Manifestations in Diabetes Mellitus - Del Rosso, Angela; Matucci Cerinic, Marco; De Giorgio, Francesca; Minari, Chiara; Maria Rotella, Carlo; Seghieri, Giuseppe (Current Diabetes Reviews, 2006)
Rheumatological manifestations of Diabetes Mellitus may be classified in: non articular, articular and bone conditions. Among non articular conditions, diabetic cheiroarthropathy, frequent in type I diabetes, the most important disorder related to limited joint mobility, results in stiff skin and joint contractures. Adhesive capsulitis of the shoulder, flexor tenosynovitis, and Duputryen's and Peyronie's diseases are also linked to limited joint mobility. Diffuse skeletal hyperostosis, due to calcification at entheses, is frequent and early, particularly in type 2 diabetes. Neuropathies cause some non articular conditions, mainly neuropathic arthritis, a destructive bone and joint condition more common in type I diabetes. Algodistrophy, shoulder-hand and entrapment syndromes are also frequent. Mononeuropathy causes diabetic amyotrophy, characterised by painless muscle weakness. Among muscle conditions, diabetic muscle infarction is a rare, sometimes severe, condition. Among articular conditions, osteoarthritis is frequent and early in diabetes, in which also chondrocalcinosis and gout occur. Rheumatoid arthritis (RA) and diabetes I have a common genetic background and the presence of diabetes gives to RA an unfavourable prognosis. Among bone conditions, osteopenia and osteoporosis may occur early in type 1 diabetes. Contrarily, in type 2 diabetes, bone mineral density is similar or, sometimes, higher than in non diabetic subjects, probably due to hyperinsulinemia.
Keywords: Limited joint mobility